Bridging thrombolysis in atrial fibrillation stroke is associated with increased hemorrhagic complications without improved outcomes. (24th November 2021) - Akbik, Feras; Alawieh, Ali; Dimisko, Laurie; Howard, Brian M; Cawley, C Michael; Tong, Frank C; Nahab, Fadi; Samuels, Owen B; Maier, Ilko; Feng, Wuwei; Goyal, Nitin; Starke, Robert M; et al.
Abstract : Background: Atrial fibrillation (AF) associated ischemic stroke is associated with worse functional outcomes, less effective recanalization, and increased rates of hemorrhagic complications after intravenous thrombolysis (IVT). Conversely, AF is not associated with hemorrhagic complications or functional outcomes in patients undergoing mechanical thrombectomy (MT). This differential effect of MT and IVT in AF associated stroke raises the question of whether bridging thrombolysis increases hemorrhagic complications in AF patients undergoing MT. Methods: This international cohort study of 22 comprehensive stroke centers analyzed patients with large vessel occlusion (LVO) undergoing MT between June 1, 2015 and December 31, 2020. Patients were divided into four groups based on comorbid AF and IVT exposure. Baseline patient characteristics, complications, and outcomes were reported and compared. Results: 6461 patients underwent MT for LVO. 2311 (35.8%) patients had comorbid AF. In non-AF patients, bridging therapy improved the odds of good 90 day functional outcomes (adjusted OR (aOR) 1.29, 95% CI 1.03 to 1.60, p=0.025) and did not increase hemorrhagic complications. In AF patients, bridging therapy led to significant increases in symptomatic intracranial hemorrhage and parenchymal hematoma type 2 (aOR 1.66, 1.07 to 2.57, p=0.024) without any benefit in 90 day functional outcomes. Similar findings were noted in a separate propensity score analysis. Conclusion: In this large thrombectomy registry, AF patients exposed to IVT before MT had increased hemorrhagic complications without improved functional outcomes, in contrast with non-AF patients. Prospective trials are warranted to assess whether AF patients represent a subgroup of LVO patients who may benefit from a direct to thrombectomy approach at thrombectomy capable centers.